Using story-based methodologies to explore physics identities: How do moments add up to a life in physics? - Allison J. Gonsalves; Anna T. Danielsson; Lucy Avraamidou; Anne-Sofie Nyström; Rebeca Esquivel (Physical Review Physics Education Research, 2023)
[This paper is part of the Focused Collection on Qualitative Methods in PER: A Critical Examination.] This article details methodologies employed to enable sharing and coconstructing the stories of three women’s lives in physics. The first case explores the usefulness of timeline interviewing, where participants narrate episodes that are coconstructed with the researcher as meaningful over time. We illustrate this method in the case of a mature student in Sweden from a working-class background who shared moments that added up to a life outside of physics and then a sharp turn into physics later in life. The second case explores life-history interviewing using a narrative-inquiry approach and deep relationship building which enabled the coconstruction of stories of experiences over time. These moments are coconstructed with the researcher and analyzed using an intersectionality lens to yield a story depicting the transnational experiences of a woman of color moving across various European contexts into the North American physics context. The final case is of a first-generation Canadian woman of color who shared her navigations of in and out of school physics via a method known as the “Rivers of Life.” Using this method, the participant narrates their experiences with physics as a river, using metaphorical tools like rafts, rocks, rapids, tributaries to discuss various moments described as twists and turns over time that together amount to a life in physics. We discuss the value of different approaches to coconstructing narratives with participants and, in particular, the need for this kind of research in physics contexts.